Pengaruh Produk dan Orientasi Pasar Terhadap Keputusan Pembelian Pada UMKM - Rahmi, Rahmi; Putra, Pandi; Nurbakti, Rezky (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This research aims to find out whether product and market orientation influence purchasing decisions among MSMEs in Pinrang district. This research uses SPSS 22 for Windows. The population in this research is consumers who buy MSME products in Pinrang Regency. The number of respondents in this study was 45 respondents, of which there were 18 men or 40% and 27 women or 60%. The sample measurements used in this research used the Roscoe formula. The results of this research show that Product and Market Orientation (X) influence Purchasing Decisions (Y). From the results of the T or partial test, the Product (X1) and Market Orientation (X2) variables partially influence purchasing decisions. Then the results of the F test or simultaneous test show the calculated F value of 17,000 which is greater than Ftable 2.83. Then to test the coefficient of determination (R2) seen from R square, namely 44.7% which is influenced by the Purchase Decision and 55.3% influenced by other variables. value of 0.000 <0.05.